Serial Serum C-reactive Protein in the Diagnosis of Neonatal Sepsis: A Cross-sectional Study - Santhakumar Sundarapandian (Indian Journal of Neonatal Medicine and Research, 2017)
Introduction: C-reactive Protein (CRP) is an acute phase reactant secreted in increased amounts in the early hours of acute inflammation. Aim: To evaluate serial CRP levels for the diagnosis of neonatal infection and to do comparative analysis of CRP levels with other parameters of sepsis screen. Materials and Methods: Neonates with birth weight >1500 g and suspected to have sepsis were included. CRP was measured from the serum by quantitative turbidimetric immunoassay. The CRP 1 level was measured at the time of clinical presentation; CRP 2 and CRP 3 were measured at 24 and 48 hours respectively. Results: A total of 100 neonates were included. CRP was positive in 72% cases (CRP 2 in 59% and CRP in 72% cases). On comparative analysis of CRP with symptomatology, culture of the body fluid, WBC count, proven sepsis; serial CRP levels showed increase in sensitivity, decrease in specificity, not much change in Positive Predictive Value (PPV), but increase in Negative Predictive Value (NPV). CRP 3 was significantly associated with culture positivity. Conclusion: Serial CRP measurements are useful in the diagnosis of neonatal sepsis. CRP 3 level may virtually rule out or rule in the diagnosis of neonatal sepsis, and has very good correlation with blood culture.